Body Composition of Adolescent of Shorter Stature - Fayasari, Adhila; Huriyati, Emy; Julia, Madarina (Pakistan Journal of Nutrition, 2019)
Background and Objective Studies have shown that adults with stunted growth have a higher risk of obesity and higher fat mass. This study aimed to assess whether stature was associated with risk of obesity and adverse body fat composition in Indonesian adolescents. Materials and Methods: This study used a cross-sectional study and included 730 adolescents aged 15-18 years in Yogyakarta, Indonesia. Data on height and body mass index (BMI) were converted to height-for-age standard deviation scores (SDS) and BMI-for-age SDS, based on the World Health Organizations (WHO) 2007 guidelines. Body fat percentage was measured with the Full Body Sensor Body Composition Monitor and Scale (Omron HBF 516, Japan), which estimated body fat percentage using Bioelectrical Impedance Analyses. Individuals were designated as shorter or taller using median height-for-age SDS with a cut-off of 1.0. BMI-for-age SD, waist circumference, waist-to-height ratio and body fat percentage were compared using t-tests. Results: There was no difference in the odds for obesity between shorter and taller adolescents. While taller adolescents had large waist circumferences, after controlling for height, shorter female adolescents had larger waist-to-height ratios. Differences in body fat percentage were not consistent across gender and nutritional status. Conclusion: There was no difference in the odds for obesity between shorter and taller adolescents. However, after controlling for height, shorter adolescents had larger waist-to-height ratios.